Cardiac hormones target nuclear oncogenes c‐Fos and c‐Jun in carcinoma cells. (2nd September 2013) - Manimala, Neil J.; Frost, Chelsea D.; Lane, Meghan L.; Higuera, Mariana; Beg, Rana; Vesely, David L.
Abstract Background c‐Fos is a cellular proto‐oncogene which dimerizes with c‐Jun proto‐oncogene to form AP‐1 transcription factor, which upregulates transcription of genes involved in proliferation and cancer formation. Four cardiac hormones, that is, long‐acting natriuretic peptide (LANP), vessel dilator, kaliuretic peptide (KP) and atrial natriuretic peptide (ANP) with anticancer effects in vivo are potent inhibitors of the Ras‐MEK 1/2‐ERK 1/2 kinase cascade and signal transducer and activator of transcription‐3 (STAT‐3) that activate c‐Fos and c‐Jun. These four cardiac hormones were investigated for their effects on proto‐oncogenes c‐Fos and c‐Jun within the nucleus of cancer cells. Materials and methods Four cardiac hormones were evaluated for their ability to decrease proto‐oncogenes c‐Fos and c‐Jun, measured by ELISA in extracted nuclei of three human cancer cell lines. Results Vessel dilator, LANP, KP and ANP over a concentration range of 100 pM–10 μM, maximally decreased c‐Fos by 61%, 60%, 61% and 59% in human hepatocellular cancer cells, by 82%, 74%, 78% and 74% in small‐cell lung cancer cells, and by 82%, 73%, 78% and 74% in human renal adenocarcinoma cells. c‐Jun was maximally reduced by vessel dilator, LANP, KP and ANP by 43%, 31%, 61% and 35% in hepatocellular cancer cells, by 65%, 49%, 59% and 40% in small‐cell lung cancer cells, and by 47%, 43%, 57% and 49% in renal cancer cells. Conclusion Four cardiac hormones are potent inhibitors of c‐Fos and c‐Jun proto‐oncogenes within the nucleus of cancer cells.